Maritime tourism space - Butowski, Leszek (Turyzm/Tourism, 2014)
The aim of this article is to provide a description of the processes which take place within offshore and coastal areas treated as contemporary tourism space. The article presents the evolution of maritime space towards the formation of maritime tourism space. It also offers a classification of maritime tourism space types according to types of sailing tourism (investigated on a global scale). The analysis has covered the main geographical-structural conditions and forms of adaptation (with particular focus on coastal areas). The analysis covered seaside areas as well, but only in the context of their functional relation with sea areas. The entire investigation was conducted from the perspective of maritime sailing tourism (yachts and other recreational crafts).